Linear-Scaling Techniques in Computational Chemistry and Physics Methods and Applications - Zalesny, Robert; Papadopoulos, Manthos G.; Mezey, Paul G.; Leszczynski, Jerzy; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Computational chemistry methods have become increasingly important in recent years, as manifested by their rapidly extending applications in a large number of diverse fields. The ever-increasing size of the systems one wants to study leads to the development and application of methods, which provide satisfactory answers at a manageable computational cost. An important variety of computational techniques for large systems are represented by the linear-scaling techniques, that is, by methods where the computational cost scales linearly with the size of the system. This monograph is a collection of chapters, which report the state-of-the-art developments and applications of many important classes of linear-scaling methods. Linear-Scaling Techniques in Computational Chemistry and Physics: Methods and Applications serves as a handbook for theoreticians who are involved in the development of new and efficient computational methods as well as for scientists who use the tools of computational chemistry and physics in their research
Including chapters on: Linear scaling second order Møller Plesset perturbation theory -- Divide-and-conquer approaches to quantum chemistry: Theory and implementation -- Mathematical formulation of the fragment molecular orbital method -- Linear scaling for metallic systems by the Korringa-Kohn-Rostoker multiple-scattering method -- Density matrix methods in linear scaling electronic structure theory -- Methods for Hartree-Fock and density functional theory electronic structure calculations with linearly scaling processor time and memory usage -- Some thoughts on the scope of the linear scaling self-consistent field electrnic structure methods -- The linear scaling semiempirical localSCF method and the finite LMO approximation -- Molecular Tailoring: an Art of the Possible for Ab Initio Treatment of Large Molecules and Molecular Clusters -- Local approximations for an efficient treatment of electron correlation and electron excitations in molecules.
Keywords: Chemistry; Chemistry; Theoretical and Computational Chemistry; Theoretical, Mathematical and Computational Physics